Fabricated Micro‐Nano Devices for In vivo and In vitro Biomedical Applications. (26th July 2013) - Barkam, Swetha; Saraf, Shashank; Seal, Sudipta
Abstract : In recent years, the innovative use of microelectromechanical systems (MEMSs) and nanoelectromechanical systems (NEMSs) in biomedical applications has opened wide opportunities for precise and accurate human diagnostics and therapeutics. The introduction of nanotechnology in biomedical applications has facilitated the exact control and regulation of biological environments. This ability is derived from the small size of the devices and their multifunctional capabilities to operate at specific sites for selected durations of time. Researchers have developed wide varieties of unique and multifunctional MEMS/NEMS devices with micro and nano features for biomedical applications (BioMEMS/NEMS) using the state of the art microfabrication techniques and biocompatible materials. However, the integration of devices with the biological milieu is still a fundamental issue to be addressed. Devices often fail to operate due to loss of functionality, or generate adverse toxic effects inside the body. The in vitro and in vivo performance of implantable BioMEMS such as biosensors, smart stents, drug delivery systems, and actuation systems are researched extensively to understand the interaction of the BioMEMS devices with physiological environments. BioMEMS developed for drug delivery applications include microneedles, microreservoirs, and micropumps to achieve targeted drug delivery. The biocompatibility of BioMEMS is further enhanced through the application of tissue and smart surface engineering. This involves the application of nanotechnology, which includes the modification of surfaces with polymers or the self‐assembly of monolayers of molecules. Thereby, the adverse effects of biofouling can be reduced and the performance of devices can be improved in in vivo and in vitro conditions. WIREs Nanomed Nanobiotechnol 2013, 5:544–568. doi: 10.1002/wnan.1227 This article is categorized under: Diagnostic Tools > Biosensing Diagnostic Tools > Diagnostic Nanodevices Nanotechnology Approaches to Biology > Nanoscale Systems in Biology